Tribo-chemical wear of various 3d-transition metals against DLC: Influence of tribo-oxidation and low-shear transferred layer - Kim, Jae-Il; Lee, Woo-Young; Tokoroyama, Takayuki; Murashima, Motoyuki; Umehara, Noritsugu (Tribology international, 2023)
Diamond-like carbon (DLC) is a promising solid lubricant owing to its excellent anti-friction and wear-resistance characteristics. However, the high hardness of DLC causes two-body abrasion to its counterpart, which generally are ferrous and brass metals having a relatively low hardness, resulting in severe wear of counterpart. Therefore, it is required to solve the wear-imbalance issue, leading to noise and vibration in tribo-system. In this study, we aimed to investigate the wear behavior of counterparts sliding against DLC. We used four-3d-transition metals (Ti, Fe, Ni, and Cu) as the counterpart of DLC, based on the chemical properties for carbon and oxygen, i.e., the activation energy of oxidation and work of separation with carbon. Our finding is suggested that the wear of transition metals was governed by oxidative wear rather than mechanical wear (e.g., adhesive wear and abrasive wear). Moreover, their oxidative wear was prevented by carbon-containing tribofilm, which is transferred from DLC continuously. It revealed that severe oxidational wear was caused in copper and iron, because of their chemical properties. [Display omitted]